Physiology and Anatomy for Nurses and Healthcare Practitioners : A homeostatic approach - Clancy, John, 1958-; McVicar, Andrew J.; Clancy, John, 1958- (London : Hodder Arnold, 2009)
Concentrating on the homeostatic principles of human physiology, this text emphasises the role of each body system in the maintenance of an optimal environment, and explains how disturbances of homeostatic mechanisms promote illness.
Rev. ed. of: Physiology and anatomy : a homeostatic approach / John Clancy, Andrew McVicar.
Includes bibliographical references and index.
Keywords: Human physiology; Human anatomy; Homeostasis